Grain Sorghum Cost-Return Budget in Western Kansas - O'Brien, Daniel M.; Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2002)
This publication projects a budget that reflects expected income and costs based on typical production of grain sorghum in western Kansas.
MF904_2002_10
Keywords: MF904; Economics; Crops; MF